2009
DOI: 10.1590/s0102-86502009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention by celecoxib in reflux-induced gastric adenocarcinoma in Wistar rats that underwent gastrojejunostomy

Abstract: Purpose:To evaluate chemoprevention by celecoxib in cases of reflux-induced gastric adenocarcinoma, in Wistar rats that underwent gastrojejunostomy. Methods: Sixty male Wistar rats of average age three months underwent surgery and were distributed into three groups: group 1, exploratory laparotomy; group 2, gastrojejunostomy; and group 3, gastrojejunostomy and daily celecoxib administration. After 53 weeks, the animals were sacrificed. Changes in the mucosa of the gastric body of group 1 and in the gastrojejun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In addition, chronic NSAID therapy may be able to reduce the risk of colon cancer by 50%, as well as the incidence of esophageal and gastric cancer (26). Studies on animals showed that celecoxib prevented and inhibited gastric cancer carcinogenesis (27,28). The results of the present study demonstrated that celecoxib inhibited the proliferation of SGC7901 gastric cancer cells.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, chronic NSAID therapy may be able to reduce the risk of colon cancer by 50%, as well as the incidence of esophageal and gastric cancer (26). Studies on animals showed that celecoxib prevented and inhibited gastric cancer carcinogenesis (27,28). The results of the present study demonstrated that celecoxib inhibited the proliferation of SGC7901 gastric cancer cells.…”
Section: Discussionsupporting
confidence: 64%
“…Steinbach et al ( 23 ) performed a double-blind, placebo-controlled clinical trial, which showed that celecoxib inhibited the formation of familial adenomatous polyposis. Animal experiments have shown that celecoxib has preventive and suppressive effects on gastric cancer ( 24 , 25 ). In the present study, the tumor inhibition rates in the 5-Fu, celecoxib and combination groups were 26.36, 59.70 and 88.37%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 is known to be associated with invasion, metastasis, apoptosis and other malignant behaviors of gastrointestinal cancers [6][7][8] . Studies have shown that COX-2 inhibitors can reverse MDR by a variety of ways and improve cell sensitivity to chemotherapeutics [9][10][11] . Some studies also demonstrated that COX-2 is related to the expression of classical MDR factors such as P-glycoprotein (P-gp), glutathione Stransferase pi (GST-π) and topoisomerase II alpha (Topo-II-α) [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%